Polymorphous billiard with chaotic beams dynamics - Naydenov, S.V.; Maslovsky, Yu.N.; Yanovsky, V.V. (Functional Materials, 2006)
A new type of billiard is introduced - the one with chaotic beams dynamics. The dynamics of dumbbell-like polymorphous billiards family is studied. The chaotic behaviour of the beams and their uniform stationary distribution are proved. The chaotic properties found let one use polymorphous billiard in physical applications.